Top Management Team Characteristics and Social Value Creation. Issue 2 (4th May 2019) - Gauthier, Jeffrey; Cohen, David; Meyer, Chris R.
Abstract: This article explores the implications of top management team (TMT) diversity and identity in fostering an organizational environment that promotes social value creation. Upper echelon theory is integrated with research on social entrepreneurship to develop propositions concerning the relationship between TMT characteristics and social value creation. In doing so, this article responds to calls to examine the role of group efforts in creating social value and offers contributions to both upper echelon theory and social entrepreneurship research.